2007
DOI: 10.1016/j.alcohol.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Language and literacy outcomes from a pilot intervention study for children with fetal alcohol spectrum disorders in South Africa

Abstract: This pilot study investigated the efficacy of a classroom language and literacy intervention in children with fetal alcohol spectrum disorders (FASD) in the Western Cape Province of South Africa. The study forms part of a larger, on-going study that includes metacognitive and family support interventions in addition to language and literacy training (LLT). For the LLT study, 65 nine year old children identified as either FASD or not prenatally exposed to alcohol, were recruited. FortyPublisher's Disclaimer: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 31 publications
2
58
0
2
Order By: Relevance
“…Findings indicated that children who received the math intervention in addition to educational support showed greater gains on mathematics outcome measures compared to those who received educational support only [Kable et al, 2007], and these gains were maintained at 6-month follow-up [Coles et al, 2009]. Adnams et al [2007] demonstrated the efficacy of a school-based, language and literacy training (LLT) intervention for 9-year-old children with FASDs in South African. In this study, 40 children with FASDs were assigned to either the intervention condition (n 5 20) or an FASD control group (n 5 20).…”
Section: Cognitive and Academic Skills Trainingmentioning
confidence: 97%
“…Findings indicated that children who received the math intervention in addition to educational support showed greater gains on mathematics outcome measures compared to those who received educational support only [Kable et al, 2007], and these gains were maintained at 6-month follow-up [Coles et al, 2009]. Adnams et al [2007] demonstrated the efficacy of a school-based, language and literacy training (LLT) intervention for 9-year-old children with FASDs in South African. In this study, 40 children with FASDs were assigned to either the intervention condition (n 5 20) or an FASD control group (n 5 20).…”
Section: Cognitive and Academic Skills Trainingmentioning
confidence: 97%
“…Proactive interventions designed to facilitate the maturation of PA in at-risk children have shown to be efficacious with at-risk groups of children (Nelson et al 2005;Adnams et al 2007;Vadasy and Sanders 2010;Collet et al 2012). With 75 % of the children with GAL investigated in this study presenting with diminished PA skills, a means of identifying which children with GAL require proactive support would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Further, proactive intervention programmes aimed at nurturing the maturation of PA (Morrow 2007) have been implemented with successful outcomes for at-risk populations such as children with Down syndrome (Lemons and Fuchs 2010), speech impairment (Al Otaiba et al 2009), specific language impairment (Collet et al 2012), minority language speakers (Vadasy and Sanders 2010), foetal alcohol spectrum disorders (Adnams et al 2007), and emotionally disturbed children (Nelson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive Control Therapy (CCT) was developed several decades ago and is designed to reorganize dysfunctional cognitive controls and strategies by teaching children how to think differently, and enhance self-observation and regulation [18][19][20]. Adnams et al [19] piloted CCT techniques in 10 children (mean age of 8 years) with Fetal Alcohol Syndrome in classrooms in South Africa.…”
Section: Self-regulationmentioning
confidence: 99%
“…Adnams et al [19] piloted CCT techniques in 10 children (mean age of 8 years) with Fetal Alcohol Syndrome in classrooms in South Africa. Children in the CCT group improved significantly in terms of teacher-rated behaviours and showed a non-significant improvement in cognitive control, but no change was noted in neuropsychological test scores.…”
Section: Self-regulationmentioning
confidence: 99%